Élaboration d’un cadre de référence pour l’étude des stratégies : analyse de l’activité et étude de cas multiples dans deux usines de crabe - Marie-Eve Major; Nicole Vézina (Perspectives Interdisciplinaires sur le Travail et la Santé)
Study of the strategies used by workers is a central aspect of work activity analysis in ergonomics. This study proposes a conceptual framework for strategy collection and analysis, and describes the nature and issues of the strategies developed by seasonal crab plant workers with musculoskeletal disorders. Based on a methodology combining the ergonomic approach of work activity analysis and a multiple case study of 16 female workers (8 in Newfoundland, 8 in Quebec), interviews and observations of the work activity and organization were conducted for two consecutive years. While showing a wide range of strategies developed by workers to manage pain (19 categories of strategies obtained), the results also showed the advantages of some strategies and the costly health compromises of other strategies. The inductively developed framework, based empirically on field data, is a tool that can be used by researchers and ergonomists to identify and classify strategies.